Sistem Rekomendasi Penentuan Titik Usaha Kafe Menggunakan Data Spasial dan Algoritma Topsis - Irfan; Amil A.Ilham; Imran Taufik; Dedi Suarna (Bulletin of Information Technology (BIT), 2023)
− The cafe business is a business that has very promising opportunities because this cafe business has a very wide target market, namely not only coffee lovers, but also ordinary people, especially millennials such as students and university students. Sinja City is a city with good business potential, but the problem is that there is no system that can determine suitable business locations, especially determining café business locations. This research aims to develop a recommendation system that can help prospective cafe entrepreneurs determine the optimal location to open their cafe business. This system uses a spatial data-based approach and the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method to produce appropriate recommendations [1]. The results of this research produce a list of recommendations for the best locations to open a cafe business. This recommendation system can help cafe entrepreneurs make more informed decisions and minimize the risks associated with choosing a business location. In addition, the use of spatial data and the TOPSIS method allows this system to produce recommendations that are more accurate and relevant to actual geographic conditions. Apart from that, the use of spatial data and the TOPSIS method allows this system to produce more accurate recommendations with a trial with 4 alternatives using the TOPSIS method. The highest ranking result is alternative 1 as a recommendation for determining the location of a cafe business location